‘The newest vital sign among pregnant women attending women wellness and research Centre in Qatar: a cross-sectional study’ - Sarah Naja (9954737) (2022)
Background Health literacy is a vital strategy to consider when designing health-promoting programs, and health literacy is a priority in Qatar’s national health agenda. In the context of pregnancy, inadequate health literacy has been linked to several adverse outcomes among pregnant women such as unplanned conception, smoking, and lack of multi-vitamin intake. Given the paucity of data, this study aimed to assess the level of health literacy and its determinants among pregnant women in the State of Qatar. Methods An analytical cross-sectional design was utilized. First, we piloted the measurement tools on 10% of the calculated sample size. Accordingly, the items of the measurement tools were revised. Next, we utilized a structured questionnaire to interview the participants about their socio-demographic characteristics, pregnancy-related factors, and the Newest Vital Sign Tool. A chi-square test was employed to investigate the association level among variables, with significance set to P < 0.05. A logistic regression model was used to identify the factors associated with a low literacy level. Results We found that almost four in 10 pregnant women (n = 138,45.4%) had inadequate health literacy. Furthermore, the insufficient level of health literacy was significantly associated with low educational background, decreased household income, and primigravida. However, uncontrolled glycaemia was the only significant predictor of inadequate health literacy through logistic regression. The scale was found to be reliable, with a calculated Cronbach’s alpha of 0.8. Conclusions Low health literacy is common among pregnant women in the State of Qatar. Thus, public health officials should focus on delivering tailored health literacy interventions to pregnant women in the country. Other Information Published in: BMC Pregnancy and Childbirth License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1186/s12884-021-03542-w